SOLVING LIMITED SPEAKING OPPORTUNITIES IN TEACHING ENGLISH AS EFL - Ilkhamova Iroda Nuritdinovna (Journal of new century innovations, 2024)
Abstract: One of the key challenges in teaching English as a foreign language (EFL) is providing students with sufficient opportunities to practice speaking the language. In many EFL contexts, students have limited exposure to English outside the classroom, and classroom time is often dominated by grammar instruction and written exercises. This can result in students struggling to develop their speaking skills and confidence. Addressing this issue is critical for helping EFL students become effective communicators in English.